1991
DOI: 10.1055/s-2007-1024710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine Ingestion on Performance and Anaerobic Metabolism during the Wingate Test

Abstract: In order to determine the effects of caffeine ingestion on performance and metabolic responses during supramaximal exercise, six healthy volunteers performed the Wingate Anaerobic Test twice. Sixty min before each trial, while in a fasting state, they took capsules containing either caffeine (5 mg/kg) or a placebo, according to a single blind and randomized procedure. Caffeine administration did not significantly change either maximal anaerobic capacity (AC) or power (AP) and power decrease (PD). It did, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
122
1
13

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 9 publications
18
122
1
13
Order By: Relevance
“…Porém, a maior parte dos estudos não encontra diferença significante da ingestão de cafeína na potência pico e potência média em sujeitos ativos (COLLOMP et al, 1991;BELL et al, 2001;GREER et al, 2006;HOFFMAN et al, 2007).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Porém, a maior parte dos estudos não encontra diferença significante da ingestão de cafeína na potência pico e potência média em sujeitos ativos (COLLOMP et al, 1991;BELL et al, 2001;GREER et al, 2006;HOFFMAN et al, 2007).…”
Section: Discussionunclassified
“…Além desses fatores, o efeito da ingestão de cafeína no sistema nervoso central (COLLOMP et al, 1991;ANSELME et al, 1992;BELL et al, 2001;DOHERTY et al, 2004;CROWE et al, 2006;SCHNEIKER et al, 2006;GLAISTER et al, 2008) por meio de alterações na percepção subjetiva de esforço poderia ser responsável pela melhora observada neste estudo, principalmente por evitar uma queda maior na intensidade durante a parte final da prova. No entanto, não foram encontradas diferenças no tempo para percorrer os últimos 40m no presente estudo.…”
unclassified
See 2 more Smart Citations
“…These results suggest that caffeine improves the cardiorespiratory function in exercising Thoroughbreds and may result in an improvement in aerobic exercise performance. Previous investigations reported that caffeine increased LA in both prolonged exercise [16,17] and intense exercise [4,18]. During anaerobic exercise, caffeine increased the production of LA by the muscle [18].…”
Section: Discussionmentioning
confidence: 99%